STRATEGIES FOR IMPROVING OIL PALM PRODUCTIVITY IN NORTH KONAWE - Rianse, Ilma Sarimustaqiyma; Zulfikar; Rianse, Usman; Arsana, Made Widana; Rustam, La Ode; Baka, Wa Kuasa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2021)
The current study was conducted to assess to assess the productivity of oil palm plantations in North Konawe, Indonesia, that are run through partnership with oil palm smallholders. Data were gathered through surveys and interviews. The study found that the productivity of the plantations was still low, ranging from 4 to 8 metric tons of fresh fruit bunch (FFB) ha–1 year–1, while the yield potential for the grown cultivars could reach 15 metric tons ha–1 year–1. Increasing the oil palm productivity could be done through improved soil capacity to provide nutrients for oil palm plants, for instance, through fertilization and/or the use of organic matter. Since the oil palm plantations were mostly developed on lands with slopes of 15-25%, activities during land preparation, cultivation, and FBBs harvest and transportation should be done properly to reduce land degradation due to erosion. Practices to minimize the sloppy land degradation include terracing and growing cover crops, multiple cropping or intercropping the main crop (oil palm) with either annual crops or perennial crops. Another strategy is through the integration of livestock farming into the oil palm plantations. Keywords: agroecology, productivity, strategy, management